2012
DOI: 10.1152/ajprenal.00130.2011
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic effect of bufalin in isolated rat kidneys involves activation of the Na+-K+-ATPase-Src kinase pathway

Abstract: Bufadienolides are structurally related to the clinically relevant cardenolides (e.g., digoxin) and are now considered as endogenous steroid hormones. Binding of ouabain to Na(+)-K(+)-ATPase has been associated, in kidney cells, to the activation of the Src kinase pathway and Na(+)-K(+)-ATPase internalization. Nevertheless, whether the activation of this cascade also occurs with other cardiotonic steroids and leads to diuresis and natriuresis in the isolated intact kidney is still unknown. In the present work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Moreover, fluorescence resonance energy transfer analyses indicated that both proteins were in close proximity, supporting a direct interaction in live cells (6). These early observations have now been confirmed by many laboratories (32)(33)(34)(35)(36)(37)(38). More recently, we have identified two potential interacting pairs between the ␣1 subunit of Na/KATPase and Src, namely the A domain/SH2 domain and the N domain/kinase domain.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, fluorescence resonance energy transfer analyses indicated that both proteins were in close proximity, supporting a direct interaction in live cells (6). These early observations have now been confirmed by many laboratories (32)(33)(34)(35)(36)(37)(38). More recently, we have identified two potential interacting pairs between the ␣1 subunit of Na/KATPase and Src, namely the A domain/SH2 domain and the N domain/kinase domain.…”
Section: Discussionmentioning
confidence: 63%
“…Many laboratories have investigated the role of Src in Na/K‐ATPase‐mediated signal transduction . Moreover, the following data indicate that the Na/K‐ATPase and Src most likely interact directly to form a functional receptor complex .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, application of CTS to the basolateral but not apical side of renal epithelial cell monolayer in culture reduces the transcellular movement of Na + . Ex vivo studies provide additional evidence of the importance of CTS and Na/K‐ATPase‐mediated signal transduction in the regulation of tubular Na + movement . Finally, studies with Dahl salt‐sensitive rats have revealed the inability of CTS in the activation of Na/K‐ATPase‐mediated signal transduction in renal proximal tubular cells, resulting in decreased ability of renal salt handling and consequently an increase in blood pressure in response to salt loading .…”
Section: Introductionmentioning
confidence: 99%
“…A status of hormone was recommended for the endogenous CSTs as it was demonstrated that it increases during exercise [108], salty meals [109][110][111], and pathological conditions such as arterial hypertension and myocardial infarction [112]. To confirm the hormone-like function, Arnaud-Batista and colleagues [113] showed that ouabain and bufalin induce diuresis, natriuresis, and kaliuresis, mediated by signal transduction in the isolated intact rat kidney. Furthermore, at the systemic level, cardenolides and bufadienolides have been implicated in many physiological and pathophysiological mechanisms, including cell growth and cancer, body or organ weight gain, mood disorders, vascular tone homeostasis, blood pressure, hypertension, and natriuresis [114].…”
Section: The Na + K + -Atpase Is the Receptor Of Hormone Ouabain 41mentioning
confidence: 99%